The role of snare proteins in cortical development. Issue 6 (5th July 2022) - Vadisiute, Auguste; Meijer, Elise; Szabó, Florina; Hoerder‐Suabedissen, Anna; Kawashita, Eri; Hayashi, Shuichi; Molnár, Zoltán
Abstract: Neural communication in the adult nervous system is mediated primarily through chemical synapses, where action potentials elicit Ca 2+ signals, which trigger vesicular fusion and neurotransmitter release in the presynaptic compartment. At early stages of development, the brain is shaped by communication via trophic factors and other extracellular signaling, and by contact‐mediated cell–cell interactions including chemical synapses. The patterns of early neuronal impulses and spontaneous and regulated neurotransmitter release guide the precise topography of axonal projections and contribute to determining cell survival. The study of the role of specific proteins of the synaptic vesicle release machinery in the establishment, plasticity, and maintenance of neuronal connections during development has only recently become possible, with the advent of mouse models where various members of the N‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE) complex have been genetically manipulated. We provide an overview of these models, focusing on the role of regulated vesicular release and/or cellular excitability in synaptic assembly, development and maintenance of cortical circuits, cell survival, circuit level excitation–inhibition balance, myelination, refinement, and plasticity of key axonal projections from the cerebral cortex. These models are important for understanding various developmental and psychiatric conditions, and neurodegenerative diseases.